Evaluation of long-term sagittal lip changes using Burstone line: Pilot Study : Lip changes using Burstone line - Sathekge, Rachel; Lesar, Colin (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2021)
Objective Lip position has become one of the most important soft tissue analyses as it influences the occlusion, tooth stability and facial aesthetic. Hence, the objective of this study was to compare the short-term and long-term sagittal lip positions/changes using the Burstone line (B-line). Methods The sample consisted of 18 Caucasoid females only (14 extractions, 4 non-extractions) who were successfully treated with edgewise appliances. All the patients were evaluated before treatment (T1),at the end of active treatment (T2), and at a long-term follow-up observation (T3). The mean age at commencement was 13.2 years with the range of 10.5-19 years. The linear distance between the tip of the lips and the B-line were measured. Results T1-T2 time intervals showed the upper lip underwent a mean change of 1.272 mm relative to the B-line (-32.8%) which was statistically significant. The lower lip showed a mean change of 1.549 mm (-22.2%), but these changes were not statistically significant. Lip protrusion relative to the B-line continued to reduce during the long term follow up period. The upper lip showed slight changes (-9.2%), whereas the lower lip demonstrated greater change (-53.8%). Conclusion Using B-line, the sagittal soft tissue lip positions were more retrusive on the long-term follow-up records for both extraction and non-extraction cases, their values were not very different from the normal values of the untreated cases. Although the differences were not statistically significant, upper lips were retrusive post treatment from T1-T2, while were statistically significant the lower lips were retrusive from T1-T2.